Teacher in-service training and re-training in Indonesia - Sumintono, B.; Subekti, N.B. (Studies and Publishing, 2014)
The history and development of teacher in-service training and re-training in Indonesia is unique. It started with emergency re-training in the Old Order era mostly for primary school teachers which was also a program to improve their qualifications. The next era featured massive and varied training programs provided by the government. The result in both eras were not encouraging